Innate immunity recovers earlier than acquired immunity during severe postoperative immunosuppression - Lachmann, Gunnar (Int J Med Sci, 2018)
Background: Postoperative immune suppression, particularly a loss of cell-mediated immunity, is commonly seen after surgery and is associated with worse outcome, i.e. delayed wound healing, infections, sepsis, multiple-organ failure and cancer recurrence. However, the recovery of immune cells focusing on differences between innate and acquired immunity during severe postoperative immunosuppression is not investigated. Methods: In this retrospective randomized controlled trial (RCT) subgroup analysis, 10 postoperatively immune suppressed patients after esophageal or pancreatic resection were analyzed. Innate and acquired immune cells, the expression of human leukocyte antigen-D related on monocytes (mHLA-DR), lipopolysaccharide (LPS)-induced monocytic TNF-α and IL-10 secretion ex vivo, Concanavalin A (Con A)-induced IFN-γ, TNF-α, IL-2, IL-4, IL-5 and IL-10 release were measured preoperatively (od) until day 5 after surgery (pod5). Recovery of immune cells was defined by a significant decrease respectively increase after a significant postoperative alteration. Statistical analyses were performed using nonparametric statistical procedures. Results: Postoperative alterations of innate immune cells recovered on pod2 (eosinophils), pod3 (neutrophils) and pod5 (mHLA-DR, monocytic TNF-α and IL-10 secretion), whereas alterations of acquired immune cells (lymphocytes, T cells, T helper cells, and cytotoxic T cells) did not recover until pod5. Peripheral blood T cells showed an impaired production of the T helper (Th) 1 cytokine IFN-γ upon Con A stimulation on pod1, while Th2 specific cytokine release did not change until pod5. Conclusions: Innate immunity recovered earlier than acquired immunity during severe postoperative immunosuppression. Furthermore, we found a more anti- than pro-inflammatory T cell function on the first day after surgery, while T cell counts decreased.